Regularities of the influence of microarc oxidation of aluminum alloys on the phase-structural state of the formed oxide coatings and the peculiarities of γ-Al₂O₃ → α-Al₂O₃ polymorphic transformation during their annealing - Sоbоl, Oleg; Subbotina, V. V. (Національний технічний університет "Харківський політехнічний інститут", 2020)
The influence of the technological parameters of microarc oxidation on the regularities of the phase-structural state of coatings formed on D16 aluminum alloys (the main alloying element is Cu) and AMg3 (the main alloying element is Mg) and the effect of annealing in the temperature range 600–1280 °C on the γ-Al₂O₃ → α-Al₂O₃ phase transformation are investigated. It was found that in the coatings formed during microarc oxidation in a complex (alkaline-silicate) electrolyte, three main phase-structural states are revealed: γ-Al₂O₃, α-Al₂O₃ and mullite (3Al₂O₃·2SiO₂). The conditions of electrolysis allowing the formation of a two-phase state (γ-Al₂O₃ and α-Al₂O₃) on alloys of both types have been determined. It has been established that alloying elements of the AMg3 alloy provide in MAO coatings a higher stability of the γ-Al₂O₃ structure in comparison with the analogous state in MAO coatings on D16 alloy. High-temperature annealing of MAO coatings made it possible to reveal a more complete phase transformation on D16 alloy, the structural basis of which is the appearance of tetragonality in the defective cubic lattice of the γ-Al₂O₃ phase. Annealing of MAO coatings stimulates the γ → α transformation with the greatest dynamics of change in the coatings obtained on D16 alloy. At the highest annealing temperature of 1280 °C (for 60 min) as a result of γ→α transformation, the relative content of the α-Al₂O₃ phase in the coating is 89 % (coating obtained on D16 alloy) and 30 % (coating obtained on AMg3 alloy). A model of the polymorphic γ-Al₂O₃ → α-Al₂O₃ transformation in aluminum oxide is proposed, based on the ordering of the metal cationic subsystem in octahedral and tetrahedral internodes and the enhancement of this process upon the weakening of the “metal–oxygen” bond as a result of the replacement of Al ions by Cu ions that have a low binding energy with oxygen. A correlation between the relative content of the α-Al₂O₃ phase and the hardness of the MAO coating was found. With the highest content of the α-Al₂O₃ phase, the hardness reaches 16000 MPa.

Досліджено вплив технологічних параметрів мікродугового оксидування на закономірності фазово-структурного стану покриттів, що формуються на алюмінієвих сплавах Д16 (основний елемент легування Cu) і АМг3 (основний елемент легування Mg) і вплив відпалів в інтервалі температур 600–1280 °С на фазове перетворення γ-Al₂O₃ → α-Al₂O₃. Встановлено, що в покриттях, що формуються при мікродуговому оксидуванні в комплексному (лужно-силікатному) електроліті, виявляються три основні фазово-структурні стани: γ-Al₂O₃, α-Al₂O₃ і мулліт (3Al₂O₃•2SiO₂). Визначені умови електролізу які дозволяють формуватися двофазному стану (γ-Al₂O₃ і α-Al₂O₃) на сплавах обох типів. Встановлено, що легуючі елементи сплаву АМг3 забезпечують в МДО-покриттях більш високу стабільність структури γ-Al₂O₃, в порівнянні з аналогічним станом в МДО-покриттях на сплаві Д16. Високотемпературний відпал МДО-покриттів дозволив виявити повніше фазове перетворення на сплаві Д16 структурною основою якого є поява тетрагональности в дефектної кубічної решітці γ-Al₂O₃ фази. Відпал МДО-покриттів стимулює γ → α перетворення з найбільшою динамікою зміни в покриттях, отриманих на сплаві Д16. При максимальній температурі відпалу 1280 °С (протягом 60 хв.) в результаті γ → α перетворення відносний вміст α-Al₂O₃ фази в покритті становить 89% (покриття, отримане на сплаві Д16) і 30 % (покриття, отримане на сплаві АМг3). Запропоновано модель поліморфного γ-Al₂O₃ → α-Al₂O₃ перетворення в оксиді алюмінію, яка заснована на впорядкування металевої катіонної підсистеми в октаедричних і тетраедричних міжвузлях і посилення цього процесу при ослабленні зв'язку "метал–кисень" в результаті заміщення іонів Al іонами Cu, які мають відносно малу енергію зв'язку з киснем. Виявлено кореляцію між відносним вмістом α-Al₂O₃ фази і твердістю МДО-покриття. При найбільшому вмісті α-Al₂O₃ фази твердість досягає 16000 МПа.
Закономірності впливу мікродугового оксидування алюмінієвих сплавів на фазово-структурний стан формованих оксидних покриттів і особливості γ-Al₂O₃ → α-Al₂O₃ поліморфного перетворення при їх відпалі
Keywords: annealing; interstices; tetragonality; polymorphic transformation; відпал; міжвузля; тетрагональність; поліморфне перетворення